2013
DOI: 10.1021/jo401559t
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Fluorescent Labeling Protocol for Complex Hydroxylated Bioactive Natural Products

Abstract: Tagging of small bioactive molecules with a fluorophore is a highly sensitive method to trace their cellular activities through real-time visual information. Here we disclose a 7-nitrobenzo-2-oxa-1,3-diazole (NBD)-based, high-yielding, one-pot labeling protocol for hydroxylated molecules using Yamaguchi coupling as the key reaction. This methodology was successfully applied on several sensitive and complex hydroxylated bioactive compounds including 7-deacetylazadiradione, simvastatin, camptothecin, andrographo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Instead, elimination of the C-14 acetoxyl group had occurred. It was later found that Yamaguchi esterification protocol (2,4,6-trichlorobenzoyl chloride/TEA/DMAP/THF) [ 21 ] could successfully give ANDRO-NBD in moderate yield (54%).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, elimination of the C-14 acetoxyl group had occurred. It was later found that Yamaguchi esterification protocol (2,4,6-trichlorobenzoyl chloride/TEA/DMAP/THF) [ 21 ] could successfully give ANDRO-NBD in moderate yield (54%).…”
Section: Resultsmentioning
confidence: 99%
“…All other chemicals of analytical grade were procured locally, in India. Extraction of neem limonoids AzaA from the neem seed kernel was performed as described by Alam et al 7-Nitrobenzo-2-oxa-1,3-diazole (NBD)-based labeled AzaA was used for gel electrophoresis experiments …”
Section: Materials and Methodsmentioning
confidence: 99%
“…Extraction of neem limonoids AzaA from the neem seed kernel was performed as described by Alam et al 39 7-Nitrobenzo-2-oxa-1,3-diazole (NBD)-based labeled AzaA was used for gel electrophoresis experiments. 40 Insect Feeding and Collection of Tissues. Actively feeding H. armigera larvae collected from fields were transferred and maintained on artificial diet (AD).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…On the other hand, though the thiolysis of NBD probes in H 2 S detection has been successful, [31][32][33][34][35][36][37][38][39][40][41][42] the rising issue whether NBD-based dyes are stable in bioimaging should be addressed, because endogenous H 2 S exists in vivo and NBDbased dyes were widely used in bioimaging. [44][45][46][47][48] Herein, we prepared a series of NBD amines and studied their thiolysis reactions in buffer solution. The reaction rates of NBD amines towards H 2 S varied from 43.2 to 0.05 M −1 s −1 or smaller values dependent on the chemical structures.…”
Section: Introductionmentioning
confidence: 99%